Border trade: the urban economy circuits in Guajará-Mirim (State of Rondônia, Brazil) and Guayaramerín (Beni Department, Bolívia) - Oliveira-Neto, Thiago; Batista-Nogueira, Ricardo José; Silva-Simões-Rafael, Carlos Eduardo; Santos-Yano, Yuji (Revista Geográfica de América Central., 2021)
Border commerce is comprised of fluxes and fixed objects within cities or along circulation routes, which creates dynamism based on the different levels of commerce ranging from the presence of “chain” stores and retail outlets, small-store sheds to informal commerce.  To elucidate the particular case of the Brazil-Bolivia border cities of Guajará-Mirim and Guayaramerín, we chose to use Santos’s (1979; 2004) proposal of urban economy circuits as the theoretical framework.